Novel evidence on the effect of tramadol on self-paced high-intensity cycling - Zandonai, T.; Holgado, D.; Ciria, L. F.; Zabala, M.; Hopker, J.; Bekinschtein, T.; Sanabria, D. (Journal of Sports Sciences, 2021)
The use of tramadol is a controversial topic in cycling. In order to provide novel evidence on this issue, we tested 29 participants in a pre-loaded cycling time trial (TT; a 20-min TT preceded by 40-min of constant work-rate at 60% of the VO2max) after ingesting 100 mg of tramadol (vs placebo and paracetamol (1.5 g)). Participants performed the Psychomotor Vigilance Task (PVT) at rest and a Sustained Attention to Response Task (SART) during the 60 min of exercise. Oscillatory electroencephalography (EEG) activity was measured throughout the exercise. The results showed higher mean power output during the 20-min TT in the tramadol vs. paracetamol condition, but no reliable difference was reported between tramadol and placebo (nor paracetamol vs. placebo). Tramadol resulted in faster responses in the PVT and higher heart rate during exercise. The main effect of substance was reliable in the SART during the 40-min constant workload (no during the 20-min TT), with slower reaction time, but better accuracy for tramadol and paracetamol than for placebo. This study supports the increased behavioural and neural efficiency at rest for tramadol but not the proposed ergogenic or cognitive (harmful) effect of tramadol (vs. placebo) during self-paced high-intensity cycling.